Internal Customer Satisfaction and Service Quality Toward Trust and Word of Mouth - Rahayu, Sri (ASEAN Marketing Journal, 2021)
This study generally aims to analyze the influence of internal customer satisfaction and perceptions of service quality in creating trust and word of mouth in higher education service industry. In the process, this study aims to achieve a special purpose, which is to build constructs/ variables to measure internal customer satisfaction, so in the future it can be applied to universally in other institutions of higher education. The results of this study indicate that the internal customer satisfaction can be measured with three constructs, namely: service product, service delivery, and service environment. All of those variables have significant relationship with trust, which is significantly related to word of mouth. On the other side, communication, productivity and responsiveness are found to be significant in measuring the perceptions of service quality.The results also proved that the perception of service quality is significantly related to trust and word of mouth. This study is expected to contribute measurement tools of internal customer satisfaction in higher ducation. This research is also expected to enrich discussion on how to measure the internal customer satisfaction and service quality toward trust and word of mouth in higher education. Thus the higher education can continue to strive to provide educational service in accordance with the expectations of the customers.